Peran Pendidikan Islam Sebagai Diseminasi Social Culture - Mukarromah Mukarromah (Journal on Education, 2023)
Islamic education is very important for Muslims themselves because they can learn science dan others. Islamic education always has a role in creating an Islamic society that has dimensions of faith dan sharia which encourage humans as individuals to have freedom dan human rights. It is also inseparable that Islamic education also plays a role as cultural socialization. Regarding the method used in this study, the researcher used a qualitative descriptive method, with a type of literature research. Because this research is a qualitative type dan was conducted in a library, the authors discussed content analysis, namely unitizing, sampling, recording, reducing, abductively inferring, dan narrating. The results of this study are that there are 4 (four) roles of Islamic education as social culture dissemination, namely; a) media for disseminating the values of religious teachings, 2) maintaining religious traditions, 3) forming morals dan personality, dan 4) bastion of national morality. Thus, Islamic education is the right method for changing attitudes dan guiding community members to accept dan initiate social cultural change.